To develop with or without the prion protein - Halliez, Sophie; Passet, Bruno; Martin-Lannerée, Séverine; Hernandez-Rapp, Julia; Laude, Hubert; Mouillet-Richard, Sophie; Vilotte, Jean-Luc; Béringue, Vincent (Frontiers in Cell and Developmental Biology, 2014)
The deletion of the cellular form of the prion protein (PrPC) in mouse, goat and cattle has no drastic phenotypic consequence. This stands in apparent contradiction with PrPC quasi- ubiquitous expression and conserved primary and tertiary structures in mammals, and its pivotal role in neurodegenerative diseases such as prion and Alzheimer’s diseases. In zebrafish embryos, depletion of PrP ortholog leads to a severe loss-of-function phenotype. This raises the question of a potential role of PrPC in the development of all vertebrates. This view is further supported by the early expression of the PrPC encoding gene (Prnp) in many tissues of the mouse embryo, the transient disruption of a broad number of cellular pathways in early Prnp-/- mouse embryos, and a growing body of evidence for PrPC involvement in the regulation of cell proliferation and differentiation in various types of mammalian stem cells and progenitors. Finally, several studies in both zebrafish embryos and in mammalian cells and tissues in formation support a role for PrPC in cell adhesion, extra-cellular matrix interactions and cytoskeleton. In this review, we summarize and compare the different models used to decipher PrPC functions at early developmental stages during embryo- and organo- genesis and discuss their relevance.